2008
DOI: 10.1002/eji.200738071
|View full text |Cite
|
Sign up to set email alerts
|

B7‐H1 restricts neuroantigen‐specific T cell responses and confines inflammatory CNS damage: Implications for the lesion pathogenesis of multiple sclerosis

Abstract: The co-inhibitory B7-homologue 1 (B7-H1/PD-L1) influences adaptive immune responses and has been proposed to contribute to the mechanisms maintaining peripheral tolerance and limiting inflammatory damage in parenchymal organs. To understand the B7-H1/PD1 pathway in CNS inflammation, we analyzed adaptive immune responses in myelin oligodendrocyte glycoprotein (MOG) 35-55 -induced EAE and assessed the expression of B7-H1 in human CNS tissue. B7-H1 -/-mice exhibited an accelerated disease onset and significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 53 publications
3
73
0
Order By: Relevance
“…Importantly, similarly to our study, they also found this phenotype to persist in the recovery phase. Interestingly, the only co-stimulatory molecule being strongly regulated during demyelination and remyelination was Cd247 (B7-H1), a known inhibitory co-stimulatory molecule (Keir et al, 2008;Magnus et al, 2005;Ortler et al, 2008). Its expression was already induced at 2WD and remained upregulated during remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, similarly to our study, they also found this phenotype to persist in the recovery phase. Interestingly, the only co-stimulatory molecule being strongly regulated during demyelination and remyelination was Cd247 (B7-H1), a known inhibitory co-stimulatory molecule (Keir et al, 2008;Magnus et al, 2005;Ortler et al, 2008). Its expression was already induced at 2WD and remained upregulated during remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…In CNS autoimmunity, genetic deletion of either B7-H1 or PD-1 renders mice more susceptible to development of EAE (24)(25)(26). B7-H1 is upregulated in inflammatory CNS lesions and critically determines local effector T cell activation, survival, and recruitment of regulatory T cells (T reg ) into the CNS, thereby limiting CNS damage (24,27).…”
mentioning
confidence: 99%
“…B7-H1 is upregulated in inflammatory CNS lesions and critically determines local effector T cell activation, survival, and recruitment of regulatory T cells (T reg ) into the CNS, thereby limiting CNS damage (24,27).…”
mentioning
confidence: 99%
“…In light of its relevance for maintenance of immune tolerance, the role of B7-H1 on APCs has been addressed in CNS autoimmunity before: In active MOG -induced EAE, B7-H1 knock-out resulted in an enhanced disease severity, which was linked to B7-H1 expressed on APCs (18). Moreover, enhanced expression of B7-H1 was observed in MS lesions and attributed to macrophages/microglial cells, as well as astrocytes (18,19). In the periphery, B7-H1 expression has been analyzed on B cells and monocytes from MS patients; here, an increased percentage of B7-H1-positive cells was found in stable versus active MS patients (20).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the well-known role of B7-H1 on APCs in control of T-cell activation and T-cell-mediated autoimmunity (16)(17)(18), we performed coculture assays using MOG-specific B cells from Th mice as APCs and MOG-specific CD4 + T cells from 2D2 mice. Surprisingly, lack of B7-H1 on antigen-presenting B cells did not result in enhanced T-cell activation as evaluated by quantification of IFN-γ production ( Fig.…”
Section: Ablation Of B7-h1 Increases Disease Incidence and Severity Imentioning
confidence: 99%